Female participation and leadership in seedbeds: metrics, barriers, and closure strategies in engineering programs (UNIMINUTO–USC interinstitutional study) - Diaz Romero, Jineth Valentina; Guzman Restrepo, Karen Yiceth; Murcia Quiroga, Maria Camila; Tarazona Galán, Héctor Orlando; Moreno Osorio, Stevens; Arboleda Duque, Andrés Felipe (LACCEI, 2025)
This study examines the participation and leadership of women students involved in Research Seedbed in two programs and universities in Cali: Industrial Engineering (UNIMINUTO) and Technology in Information Systems and Software (Universidad Santiago de Cali, USC). A sequential explanatory mixed-methods design combined surveys (n = 120) and semi-structured interviews (n = 24) to estimate participation metrics, characterize academic and sociocultural barriers, and assess the perceived effectiveness of institutional strategies aimed at closing gaps. Results indicate that participation increases with academic progression; leadership roles are heterogeneously distributed, with greater presence in coordination and project lead positions; and barriers cluster around academic workload, inflexible schedules, and the presence of biases/microaggressions. Formal mentorship, personalized tutoring, and incentives/scholarships are associated with improvements in retention and continued engagement in research groups. Interpretation is grounded in frameworks on motivation, communal goal congruity, implicit bias, and organizational culture. Building on these results, we prioritize actions: strengthening mentorship with female role models; increasing curricular and scheduling flexibility; consolidating psychosocial support pathways; and reinforcing protocols addressing discrimination. The study provides comparable UNIMINUTO–USC indicators and a baseline for longitudinal monitoring and evaluation of academic performance and professional placement.